Room for Improvement: Rates of Birth Cohort Hepatitis C Screening in Primary Care Practices—A WWAMI Region Practice and Research Network Study. (October 2019) - Cole, Allison M.; Keppel, Gina A.; Baldwin, Laura-Mae; Gilles, Ryan; Holmes, John; Vance, Chardonnay; Kriesgman, Bill; Linares, Adriana; Hornecker, Jaime; Paddock, Elizabeth; Gerrish, Winslow; Alto, William; et al.
Introduction: An estimated 2.4 million people in the United States live with hepatitis C. Though there are effective treatments for chronic hepatitis C, many infected individuals remain untreated because 40% to 50% of individuals with chronic hepatitis C are unaware of their hepatitis C status. In 2013, the United States Preventive Services Task Force (USPSTF) recommended that adults born between 1945 and 1965 should be offered one-time hepatitis C screening. The purpose of this study is to describe rates of birth cohort hepatitis C screening across primary care practices in the WWAMI region Practice and Research Network (WPRN).Methods: Cross-sectional observational study of adult patients born between 1945 and 1965 who also had a primary care visit at 1 of 9 participating health systems (22 primary care clinics) between July 31, 2013 and September 30, 2015. Data extracted from the electronic health record systems at each clinic were used to calculate the proportion of birth cohort eligible patients with evidence of hepatitis C screening as well as proportions of screened patients with positive hepatitis C screening test results.Results: Of the 32 139 eligible patients, only 10.9% had evidence of hepatitis C screening in the electronic health record data (range 1.2%-49.1% across organizations). Among the 4 WPRN sites that were able to report data by race and ethnicity, the rate of hepatitis C screening was higher among African Americans (39.9%) and American Indians/Alaska Natives (23.2%) compared with Caucasians (10.7%; P < .001).Discussion: Rates of birth cohort hepatitis C screening are low in primary care practices. Future research to develop and test interventions to increase rates of birth cohort hepatitis C screening in primary care settings are needed.